Pengaruh Karakteristik Sistem Informasi Akuntansi Manajemen (Broad Scope, Timeliness, Aggregation, dan Integration) terhadap Kinerja Manajerial UMKM - Afandi, Akhmad Aziz; Mubarok, Abdulloh (Majors Accounting, Faculty of Economics and Business, Universitas Pancasakti Tegal, 2020)
The purpose of this study was to determine the Effect of Characteristics of Management Accounting Information Systems (Broad Scope, Timeliness, Aggregation, and Integration) on Managerial Performance of MSMEs (Study on MSMEs in Talang District, Tegal Regency). This research uses quantitative methods, with a population of 222 MSMEs in Talang District, Tegal Regency. The sampling technique using Slovin formula obtained as many as 69 respondents. The data collection method uses a questionnaire. Data processing techniques in this study using multiple linear regression with the help of analytical tools in the form of SPSS. The results of this study can be concluded that Broad Scope has a positive effect on managerial performance, because broad scope has a sig value of 0,000 <0.025 so that H1 is accepted. Timeliness has a positive effect on managerial performance, because timeliness has a sig value of 0.033> 0.025 so H2 is rejected. Aggregation has a positive effect on managerial performance, because aggregation has a sig value of 0.008 <0.025 so that H3 is accepted. Integration has a positive effect on managerial performance, because integration has a sig value of 0.003 <0.025 so that H4 is accepted.